Quantification of Self-Healing Effect of Bacillus Subtilis on Cementitious Material - Venkatraman, G.; Vanathi, V. (International Journal of Sustainable Construction Engineering and Technology, 2022)
In this paper, the self-healing ability of the bacterial concrete is tested and compared numerically with the conventional concrete. Micro-cracks cause degradation of strength which leads to deterioration of structures. To improve the life span of structures, self-healing techniques are used. One such technique is bacterial concrete which remediates cracks in concrete by using microbes as the self-healing agent. The self-healing agent is embedded into the cement mortar and its behaviour is studied. Control and bacterial specimens are cast and the tests like compressive strength, porosity, UPV test, ESEM, EDAX are done. ESEM and EDAX results show that the calcium precipitates formed in the micro-cracks at micron levels, to initiate the self-healing of mortar. UPV results show 3.90% of healing at the end of 45 days.